Phyllosphere microbial communities are modulated by pathogen coinfection, but not a plant defense hormone - Julie K. Geyer; Rita L. Grunberg; Charles E. Mitchell (PLoS ONE, 2026)
Phyllosphere microbial communities play important roles in plant health, yet the roles of plant defense hormones and coinfections in shaping these communities remain unclear. This study investigated how exogenous application of the plant defense hormone salicylic acid and fungal coinfection influenced microbial communities on leaves of tall fescue. In a factorial experiment, we treated leaves with salicylic acid (at 100 mg/L) or a control solution and inoculated them with one of four inoculation treatments: Rhizoctonia solani alone, mock inoculation, co-inoculation with both R. solani and Colletotrichum cereale , or mock co-inoculation. We characterized the fungal and bacterial communities using ITS and 16S rRNA gene sequencing, respectively. Salicylic acid application did not significantly alter the diversity, composition, or taxa abundances of either fungal or bacterial communities. In contrast, co-inoculation significantly shifted fungal community composition and increased fungal diversity compared to inoculation with R. solani alone. Bacterial communities were not significantly impacted by either inoculation treatment. These results suggest that in this system, coinfection has a stronger influence on phyllosphere fungal communities than exogenous salicylic acid application. Our findings highlight the potential for pathogen coinfections to shape plant-associated microbial communities, particularly fungi, and emphasize the need for further research on the effects of salicylic acid across different host species and experimental approaches.